Planning, a Fundamental Process in the Self-Regulation of Learning in Secondary Education - Ortiz Espinal, Natalia (2024)
This article discloses the results of an investigation whose objective was to analyze the effects of planning as a relevant part of self-regulation in the learning processes of secondary school students in the rural and urban sectors of Colombia. The research approach was mixed, which implied the collection and systematization of quantitative and qualitative data, as well as their association and analysis. Moreover, the investigators collected the data through instruments such as a questionnaire and a semi-structured interview, in which they used a focus group technique. These instruments were applied to 307 students and 71 educators from ten educational institutions from different departments of Colombia. In addition, the authors achieved data systematization through techniques such as open and axial coding in categorical analysis matrices. The analysis linked relevant methodological procedures such as identification of recurrences, coincidences, and trends; labeling and prioritization of emerging and final findings; and theoretical triangulation. The results show that although self-regulation consists of a capacity developed in the students, the teacher is decisive in awakening said capacity. It is the educator who must know what are the transversal, technological, methodological, and pedagogical components that each student requires according to their learning styles to actively empower and motivate themselves in everything that involves self-controlled planning of the development of the task. Therefore, teachers must recognize these components and thus be able to act accordingly and generate teaching-learning strategies, as well as educational environments where the students are the main actors who analyze and establish the most suitable tools, actions, and work routes for successfully facing their academic process.